RATIO OF NEUTROPHIL TO LYMPHOCYTE COUNT AS A PREDICTOR OF LENGTH OF HOSPITAL STAY IN ACUTE CHOLECYSTITIS - Khomusi, Munira Murtaza; Perveen, Sughra; Iqbal, Mazhar; Ahmed, Tanweer; Seth, Uzma Shamim; Ali , Jehangir (Infectious Diseases Journal of Pakistan, 2022)
Background: The objective was to find out the ratio of neutrophil to lymphocyte count as a predictor of length of hospital stay in acute cholecystitis. Material and Methods: This was a cross sectional observational study conducted in Ward-3 Jinnah Postgraduate Medical Centre, Karachi from November 2020 to April 2021. All patients between thirty to fifty years of age diagnosed as acute cholecystitis on basis of history, clinical examination and ultrasound abdomen were included. All Patients were treated with intravenous fluids, antibiotics and analgesics. Patients were discharged when pulse rate returned to normal and temperature and tenderness disappeared. They were advised interval cholecystectomy after six weeks. Hospital stay was recorded in days for patients with deranged neutrophil to lymphocyte ratio of greater than three. Length of stay for patients with normal ratio, lesser than three was also recorded. Age, gender, history, tenderness, differential leucocyte count and length of hospital stay were also recorded on preprinted forms. Results were analyzed by SPSS Version 25. Results: A total of ninety patients were included, ten being male (11.11%) and eighty female (88.88%). Patients with deranged ratios were sixty-five (72.22%) and normal ratios were twenty-five (27.77%). The length of hospital stay was recorded as five to eight days for deranged ratio and three to five days for normal ratio respectively. Ten patients (11.11%) had gangrenous gall bladder and underwent open cholecystectomy. Conclusion: Neutrophil to lymphocyte ratio of greater than three corresponds to longer hospital stay and complications. Keywords: Cholecystitis, Length of stay, Neutrophil -to-lymphocyte ratio